Sie sind auf Seite 1von 100

Chapter 2 MATHEMATICAL FOUNDATION

2-1 (a) Poles:

s = 0, 0, -1, -10;

(b) Poles:

s = -2, -2;

Zeros:

s = -2, , , .

Zeros:

s = 0.

The pole and zero at s = -1 cancel each other.

s = 0. The pole and zero at s = - 1 cancel each other. (c)

(c) Poles:

s = 0, -1 + j, -1 - j;

Zeros: s = -2.

(d) Poles:

s = 0, -1, -2, .

j; Zeros: s = - 2. (d) Poles: s = 0, - 1, - 2, •

2-2 (a)

 

G

(

s

)

=

(d)

 

G

(

s

) =

2-3 (a)

5

(b)

(

s

+

1

5

)

2

s

2

+

4

G

(e)

(

s

)

G

(

=

s

(c)

4

s

1

+

(

s

2

+

4

)

s

+

2

)

=

Â

k

0

=

e

kT

(

s

+

5

)

=

1

1

-

e

-

T

(

s

+

5

)

g

( )

t

=

u

( )2(

t

-

u

t

-

1)

+

2

u

(

t

-

2)

-

2

u

(

t

-

3)

G

(

g

T

s

)

( )

t

=

s

1

s

=

u

(

s

sss

1

-

sss

-

-

222

+

eee

-

-

2

3

( )2(

t

t

-

u

s

-

1)

+

u

s

(

t

-

+

L

)

=

1 -

s

(

1 +

- s

e

)

2)02

£

t

£

+ L

- s

e

G

T

s

( )

=

1

s

(

1

-

2

e

-

s

+

e

-

2

s

)

=

1

s

(

1

-

e

-

s

)

2

1

G

(

s

) =

4

s

2

+

4

s

+

8

 

-

s

g

(

t

)

=

Â

 

g

T

(

t

-

2

k

)

u

s

(

t

-

2

k

)

 

G

(

s

)

=

Â

1

(

1

-

e

-

s

)

2

e

-

2

ks

 

=

1

-

e

-

s

g

t

( )

k

=

=

2

0

tu

s

(

t

)

-

4(

t -

0.5)

u

k

0

=

s

(

t -

0.5)

+

4(

t -

1)

u

(

t -

1)

-

4(

t -

1.5)

u

sss

(

t -

s

(

1

+

1.5)

e

)

+ L

 
   

2

(

1

 

-

0.5

s

-

s

-

1.5

s

)

2

(

1 -

- 0.5 s

e

)

 

G

(

s

)

=

s

2

-

2

e

+

2

e

-

2

e

+

L

=

s

2

(

1 +

e

-

0.5 s

)

g

T

(

t

)

= 2

tu

s

(

t

)

- 4 (

t

- 0 .5)

u

s

(

t

- 0 .5)

+ 2(

t

- 1 )

u

s

(

t

- 1 )

0 £

 

t

£

1

 

2

(

 

-

0.5

s

 

-

s

2

-

0.5

s

) 2

 
 

G

T

(

s

)

=

 

2

1

-

2

e

)

(

1

+=-

e

2

e

 

s

 

s

2

2

 

)

 
 

2

(

1

-

e

-

0.5 s

)

2

-

e

ks

 

(

1 -

- 0.5 s

e

 

( )

g t

 

=

Â

 

g

T

(

t

-

k

)

u

s

(

t

-

k

)

 

G

(

s

)

=

Â

2

 

=

 

-

0.5 s

 

k

=

0

 

k

=

0

s

s

(

1 +

e

)

 

g

(

t

) = (

t

+ 1 )

u

 

(

t

) -

(

t

- 1 )

u

 

(

t

- 1 ) -

2

u

(

t

- 1 ) -

(

t

- 2 )

u

(

t

- 2 ) + (

t

- 3)

u

(

t

- 3) +

u

(

t

- 3)

 
 

s

s

s

s

s

s

 
   
 
 

1

(

 

-

s

2

-

s

-

3

s

1

-

s

-

3

s

)

 
 

G

(

s

)

=

2

1

-

e

 

-

e

+

e

)

(

1

+-+

e

2

e

 

s

s

 

2

1

1

1

1

1

 

(

 

+

5

 

+

4

)

F

(

 

)

=

 

F

(

s

)

=

 

s

s

s

 

=

+

-

 

s

+

2

 

(

s

+

1

)(

s

+

2

)(

s

+

4

)

6(

s

+

4

)

3

(

 

s

+

1

)

2(

s

+

2

)

 

f

(

t

) =

1

e

-

4

t

+

1

e

-

t

-

1

-

e

2

t

t

0

 

6

 

3

2

 

1

 

1

(

s

) -

 

x

1

(

0

) =

X

2

(

s

)

x

1

(

0

) =

1

sX

2

(

s

) -

x

2

(

0

) = -

2

X

1

(

s

) -

3

X

2

(

s

) +

 

x

2

( 0 )

= 0

 

s

Solving for X 1 (s) and X 2 (s), we have

 
 

2

 

s

 

+

3

s

+

1

1

 

1

1

 

X

1

(

s

)

=

   
 

=

 

+

-

 

s

(

s

+

1

)(

s

+

2

)

 

2

s

s

+

1

2(

s

+

2

)

 

-

1

-

1

1

 

X

2

(

s

)

=

 
 

=

+

 

(

s

+

1

)(

s

+

2

)

s

+

1

s

+

2

Taking the inverse Laplace transform on both sides of the last equation, we get

 
 

x

1

(

t

)

= 0.5 +

e

-

t

- 0.5

e

-

2

t

t

0

x

2

(

t

) = -

e

-

t

+

e

-

2

t

t

0

 

sX

(b)

2-4

2-5 (a) Taking the Laplace transform of the differential equation, we get

(b)

2

2-6 (a)

2-7

2-8

(b)

(c)

(d)

(e)

 

1

1

1

1

1

 

G

(

 

)

=

 

(

t

) =

 

s

 

-

+

g

 

-

e

 

3 s

 

2(

s

+

2 )

3

(

s

+

3)

 

3

2

 

-

.

2 5

 

5

.

2 5

 

-

t

( s

)

=

 

+

2

+

g

(

t

)

= -

2

.

5

e

 

s

+

 

1

(

s

+

1

)

s

+

3

(

s

)

=

(

50

 

-

20

-

30

s +

2

20

)

e

-

s

( )

g t

=

[

50

-

 
 

s

s

+

1

 

s

+

4

   
 

1

s

-

1

1

1

s

( s

) =

 

-

=

+

 

-

 
 

2

 

2

2

 

s

s

+

s

+

2

s

s

+

s

+

2

s

+

s

+

2

( )

 

=

1

+

1.069

e

-

0.5

t

[

sin1.323

t

+

sin

(

1.323

t

-

69.3

o

)]

G

G

G

g t

-

+

20

=

g

(

t

) =

0 5

.

t

2

e

-

t

t

0

A

=

È

Í

Í

Í

Î

- 1

0

1

---

2

-

2

3

0

3

1

˘

˙

˙

˙ ˚

B

=

È

Í

Í

Í Î

0

1

0

0

0

1

˘

˙

˙

˙ ˚

t

5

-

+

te

(

t

0.5 t

-

e

=

È

Í Î

u

u

(

1

2

(

(

t

t

)

)

˘

˙ ˚

t

t

-

0

2

1

3

e

-

3

t

-

t

+

2 5

.

e

-

3

t

 

t

0

1)

-

5sin2 (

t

-

1)

]

u

s

-

1)

-

30cos2 (

e

Taking the inverse Laplace transform,

1

+

1.447sin1.323

t

-

cos1.323

t

)

( )

u t

(a)

(c)

Y

s

( )

3

s +

1

=

R

( )

3

ssss

+

2

2

+

5

+

6

Y

(

s

)

R

(

s

)

=

s

(

s +

2)

s

4

+

10

s

3

+

2

s

2

+

s

+

2

(b)

(d)

Y

(

s

)

5

R

(

s

)

=

s

4

+

10

s

2

+

s

+

5

Y

(

s

)

1

+

2

e

- s

 

=

R

(

s

)

2

s

2

+

s

+

5

3

(

t -

t

1)

0

4

4

5

5

6

6

7

7

8

8

9

9

10

10

11

11

12

12

13

13

Chapter 4 MATHEMATICAL MODELING OF PHYSICAL SYSTEMS

4-1

(a) Force equations:

 

f

t

( )

=

M

 

d

2

y

1

+

B

 

dy

1

+

B

Ê

Ë Á

dy

dt

1

dy

2

ˆ

˜

K

(

-+-

y

y

)

 

1

dt

2

1

dt

3

dt

¯

1

2

 

Ê

Ë Á

dy

1

-

dy

 

ˆ

(

 

d

2

y

2

+

B

dy

 
 

B

2

¯ ˜

+

K

y

-

y

)

+

M

2

 

3

dt

 

dt

1

2

 

2

dt

2 2

dt

 

Rearrange the equations as follows:

 
 

d

2

y

1

(

B

1

+

B

3

)

dy

1

 

B

3

dy

2

K

(

y

1

)

f

   
 

dt

2

= -

 

M

1

dt

+

M

1

dt

-

M

1

-

y

2

+

M

1

d

2

y

2

B

3

 

dy

1

 

(

B

2

+

B

3

)

dy

2

K

(

y

1

-

y

2

)

 
   
 

dt

2

=

M

-

+

dt

M

dt

M

222

(i) State diagram: Since y

1

 

-

y

2

appears as one unit, the minimum number of integrators is three.

as one unit, the minimum number of integrators is three. dx 1 dt = - x

dx

1

dt

= -

x

2

+

(ii)

State equations:

Define the state variables as x

1

=

y

1

-

y

2

,

x

2

=

dy

2

,

x

3

=

dy

1

.

 

dt

dt

x

3

dx

2

=

K

x

1

-

(

B

2

+

B

3

)

x

2

+

B

3

x

3

 

dt

M

2

M

2

M

2

State variables:

x

1

=

y

2

,

x

2

=

dy

2

,

x

3

 

dt

State equations:

 
 

dx

dx

K

 

1

= x

2

= -

 

x

 

2

 

dt

dt

 

M

 
 

2

 

dx

dx

K

 

3

= x

 

4

=

x

 

4

1

 

dt

dt

 

M

 

1

dxKB

(

B

+

B

3

)

1

 

3

+

 

3

1

 

= -

x

1

 

x

2

-

dt

 

M

1

1

=

y

1

,

x

4

=

dy

1

.

 

dt

 

B

+

B

K

B

-

2

3

x

+

x

+

3

1

2

3

 

M

M

M

2

2

2

 

B

K

B

+

B

+

3

x

-

x

-

1

3

x

 

2

3

4

 

M

 

M

 

M

 
 

1

1

1

1

x

4

+

1

M

1

f

x

3

+

MMM

State diagram:

14

f

Y 1 ( s ) F Y 2 ( ( s s ) ) F

Y

1

(

s

)

F

Y

2

(

(

s

s

)

)

F

(

s

)

Transfer functions:

 

M

2

s

2

+

(

B

2

+

)

BsK

3

+

 

{

sMM s

1

2

3

+ B

1

 

+

B

3

)

M

2

+

(

B

2

+

B

3

)

M

1

]

s

2

+

[

K

(

B s

3

+

M

1

K

)

+++

2

1

2

M

B B

B B

2

3

+

B B

1

3

]

s

+

(

B

1

+

B

2

)

K

}

 

{

M

1

M s

2

3

2

}

s

+ B

d

2

y

1

1

+

(

B

3

B

1

)

M

2

+

B

2

+

)

(

B

dy

1

2

+

B

3

B

2

)

M

dy

2

1

]

s

1

+

[

K

(

M

1

)

+++

2

1

2

M

B B

dy

2

dy

1

B B

2

K

3

+

B B

1

3

]

s

+

(

B

1

+

B

2

)

K

   

f

 

y

 
 

dt

2

= -

 

M

 

dt

 

+

M

dt

+

M

 

dt

=

dt

-

B

2

2

= [(

= [(

(b) Force equations:

(i) State diagram:

2 = [ ( = [ ( (b) Force equations: (i) State diagram: Define the outputs

Define the outputs of the integrators as state variables, x

1

=

State equations:

dx K

1

dt

= -

B

2

x +

x

1 2

dx K

2 = -

dt

M

y

2

,

x

2

=

dy

1

dt

.

B 1

x -

1

x +

1 2

M M

f

(ii) State equations: State variables:

dx

1

dt

= -

K dx

x +

x

1 3

2 =

B dt

2

x

x

1

3

=

y

2

,

x

2

=

y

1

,

dx K

3 = -

dt

M

dy

1

x

3

x -

=

B

1

M

dt

x

.

+

1 3

Transfer functions:

15

1

M

f

Y

1

(

s

)

F

(

s

)

 

B s

2

+

K

 

s

Î È

MB s

2

2

+

(

B B

1

2

+

KM

)

s

+

(

B

1

+

B

2

)

K

˚ ˘

(c)

Force equations:

 
 

dy

1

=

dy

2

+

1

f

d

2

y

2

= -

dt

dt

 

B

1

dt

2

 

=

(i) State diagram:

 

Y

2

(

s

)

B

2

F

(

s

)

=

M B s

2

2

+

(

B B

1

2

+

)

KM s

+

(

B

1

+

B

2

)

K

(

B

1

+

B

2

 

)

dy

2

B

1

dy

2

B

1

dy

1

K

 

++-

 

y

2

 

M

 

dt

 

M

 

dt

M

dt

 

M

  dt   M   dt M dt   M State equations: Define the outputs of

State equations:

Define the outputs of integrators as state variables.

dx

dx

 

1

=

x

2

= -

 

2

dt

dt

K

M

x

1

-

B

2

M

x

2

+

1

M

f

(ii) State equations: state variables:

 

x

1

dx

1

dx

 

1

=

x

+

f

 

2

=

x

 

3

 

3

dt

B

dt

 

1

State diagram:

=

y

1

,

x

dx

2

3

dt

=

y

= -

2

,

K

M

x

x

2

3

-

=

dy

2

dt

B

2

M

x

3

.

+

1

M

f

3 dt = y = - 2 , K M x x 2 3 - =

4-2

Transfer functions:

(

Y 1 Ms

s

=

F

( s

)

+

(

(

)

2

)

BBsK

1

+

2

+

)

B s

1

Ms

2

+

B s

2

+

K

(a) Force equations:

16

Y

2

(

s

)

1

=

F

(

s

)

Ms

2

+

B s

2

+

K

y

1

=

1

K

2

(

f

+

Mg

State diagram:

)

+

y

2

d

2

y

2

dt

2

= -

B

dy

2

M

dt

-

K

<